DIMENSIONS OF CADRE SATISFICATION WITH THE WEB-BASED e-POSYANDU CADRE HEALTH APPLICATION (ePoK-K) AS AN ALTERNATIVE FOR RECORDING AND REPORTING POSYANDU ACTIVITIES - Damayanti, Melly; Saputri, Nurul Aini Suria; Darwitri (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Recording and reporting is one of the responsibilities of posyandu cadres. Every month, data is collected and reported in order to monitor and evaluate the posyandu program. Because this activity is performed manually by cadres, it has the potential to cause data errors and inaccuracies. As a result, researcher is interested in developing applications that can assist cadres in recording and reporting, so that cadres can produce accurate and valid posyandu reports. Objective: The objective of this study was to assess cadre satisfaction with the Cadre Health e-Posyandu Application (ePoK-K) as an alternative to recording and reporting posyandu activities. Method: This was a quasi-experimental study with a one-group posttest-only design. From June to August 2022, the research was conducted in the Work Area of the Mekar Baru Health Center in Tanjungpinang City. A total of 60 respondents were obtained from 12 posyandu in the Work Area of the Mekar Baru Health Center in Tanjungpinang City using a proportional stratified random sampling technique. Results: The analysis of the dimensions of respondents' satisfaction with the ePoK-K application revealed that satisfaction was very satisfied in each dimension, with the following details: tangible dimension 90%; reliability 91.7%; responsiveness 91.7%; assurance 76.7%; and empathy 83.3%. In general, respondents' satisfaction with the ePoK-K Application was very high (86.7%). Conclusion: Respondents were extremely pleased with the website-based ePoK-K application for recording and reporting posyandu activities. Keywords: Satisfaction, cadres, application